A MODEL EVALUATION OF JUDGE PERFORMANCE THROUGH JOB SATISFACTION AND JOB MOTIVATION IN THE RELIGIOUS COURT OF WEST SUMATERA - Rahmel Fitri; Hendra Lukito; Tedi Hidayat (Halu Oleo University, 2023)
A sustainable decline in judges’ performance is very risky for the future of justice, especially in the religious context. Therefore, the present study aims to evaluate religious judges’ performance by the impact of job satisfaction and job motivation. The questionnaires were distributed on two target criteria. They are 32 persons on each, so a total of 64 judges have participated. The questionnaire distribution process is online, then the feedback data is analyzed with the assistance of SPSS’s latest version. The result stated job satisfaction has no significant effects on judge performance, both mutation within province and inter-province. While job motivation has a significant effect on judge performance who have experienced mutation within and inter-province. These results suggest future research to investigate another factor that affects performance in the religious court because judge performance is really important to the effectiveness of religious courts.